β‐defensin‐2 in breast milk displays a broad antimicrobial activity against pathogenic bacteria - Joanna Baricelli; Miguel A. Rocafull; Desiree Vázquez; Betsi Bastidas; Estalina Báez‐Ramirez; Luz E. Thomas (Brazilian Society of Pediatrics, 2015)
Objective: To describe the antimicrobial activity of β‐defensin‐2 produced in the mammary gland and secreted in human breast milk. Methods: The peptide production was performed by DNA cloning. β‐defensin‐2 levels were quantified in 61 colostrum samples and 39 mature milk samples from healthy donors, by an indirect enzyme‐linked immunosorbent assay (ELISA). Using halo inhibition assay, this study assessed activity against seven clinical isolates from diarrheal feces of children between 0 and 2 years of age. The activity of β‐defensin‐2 against three opportunistic pathogens that can cause nosocomial infections was determined by microdilution test. Results: The peptide levels were higher in colostrum (n = 61) than in mature milk samples (n = 39), as follows: median and range, 8.52 (2.6‐16.3) μg/ml versus 0.97 (0.22‐3.78), p < 0.0001; Mann‐Whitney test. The recombinant peptide obtained showed high antimicrobial activity against a broad range of pathogenic bacteria. Its antibacterial activity was demonstrated in a disk containing between 1-4 μg, which produced inhibition zones ranging from 18 to 30 mm against three isolates of Salmonella spp. and four of E. coli. β‐defensin‐2 showed minimum inhibitory concentrations (MICs) of 0.25 μg/mL and 0.5 μg/mL for S. marcescen and P. aeruginosa, respectively, while a higher MIC (4 μg/mL) was obtained against an isolated of multidrug‐resistant strain of A. baumannii. Conclusions: To the authors' knowledge, this study is the first to report β‐defensin‐2 levels in Latin American women. The production and the activity of β‐defensin‐2 in breast milk prove its importance as a defense molecule for intestinal health in pediatric patients.